Analisis Potensi Kewirausahaan Di Desa Bhuana Jaya Tenggarong Seberang - Inayah, Nur; Reza, Reza; Abu, Ilham (Faculty of Teacher Training and Education, Mulawarman University, 2024)
This research is a descriptive study with a qualitative approach. Data was collected through interviews, and data analysis was conducted using data collection, data reduction, and conclusion drawing techniques. Based on the research results, it is known that Desa Bhuana Jaya's entrepreneurial potential is measured by three indicators: the businesses being run, the environment, and human resources. In terms of the types of businesses being run and have potential to be run, Desa Bhuana Jaya has a variety of businesses, ranging from culinary businesses, grocery businesses, and other businesses with a turnover that is sufficient to meet living needs and business development. Meanwhile, the physical and social environment of Desa Bhuana Jaya as a business support is very good, with existing road and lighting facilities and a clean location, although some roads are still made of earth and have not received full attention from the government. The social environment is good with no conflicts, crimes, or criminal acts. In terms of human resources, Desa Bhuana Jaya has the ability to manage businesses, including financial management, but there has been no innovation or use.